Method for testing iron content in lithium iron phosphate
The proposed method for testing iron in phosphates through sample processing and UV spectroscopy addresses the challenges of reagent safety and stability in existing methods, providing a more accurate and efficient analysis.
Patent Information
- Application Number
- CN202411667891.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-03-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing methods for testing the iron content in phosphates, such as chemical titration and ICP spectroscopy, face issues with reagent usage harming human health and unstable results due to high dilution requirements.
A method involving sample carbonization and calcination, followed by acid treatment and dilution, using UV spectroscopy with specific reagents like salicylic acid and neophenine to determine iron content, reducing reagent usage and improving stability.
This method enhances the accuracy and stability of iron content testing in phosphates, reducing reagent consumption and operational complexity while maintaining high precision.
Smart Images

Figure BDA0005145055440000021 
Figure BDA0005145055440000051 
Figure BDA0005145055440000071
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium batteries, and in particular to a method for testing the iron content in lithium iron phosphate. Background Art
[0002] In the prior art, the test methods for the iron content in lithium iron phosphate include chemical titration or ICP spectrometer testing. Among them, the chemical titration method implements the chemical analysis method adopted in the industry standard HG 4071-2021 "Iron Phosphate for Batteries": using stannous chloride under strong acidic conditions to remove most of the Fe in the test solution. 3+ Reduction to Fe 2+ Sodium tungstate was used as an indicator and titanium trichloride was used to further convert Fe 3+ Reduction to Fe 2+ , then use sodium diphenylamine sulfonate as an indicator and use potassium dichromate standard titration solution until the solution turns stable purple, which is the end point. The iron content is calculated based on the consumption of potassium dichromate standard titration solution. This method uses a lot of reagents in the intermediate process, and the use of reagents will cause certain damage to human health. Although the ICP spectrometer test method is easy to operate, it needs to add nitric acid and perchloric acid to dissolve and dilute the sample by more than 10,000 times during the test, resulting in poor stability of the test results.
[0003] Therefore, it is very necessary to obtain a method for testing the iron content in lithium iron phosphate with good testing stability and simple operation. Summary of the invention
[0004] The object of the present invention is to solve the above problems and provide a method for testing the iron content in lithium iron phosphate, which has good test stability and is easy to operate.
[0005] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows:
[0006] A method for testing the iron content in lithium iron phosphate comprises the following steps:
[0007] S1, preparing a test solution: carbonizing the test sample at a first temperature, and then ashing the test sample at a second temperature until white ash is formed to obtain an intermediate product; adding a 1:1 hydrochloric acid solution to the intermediate product, and evaporating the solution in a water bath; adding water to the evaporated intermediate product, heating and boiling the intermediate product, transferring the solution to a volumetric flask, and diluting the solution to the scale with water to obtain a test solution;
[0008] S2, determine the iron content in the solution to be tested: measure 5.0 mL of the obtained solution to be tested and place it in a 50 mL volumetric flask, add 1 mL of 1 mol / L hydrochloric acid solution, 1 mL of 10 wt% hydroxylamine hydrochloride, 1 mL of 0.12 wt% o-phenanthroline solution to the volumetric flask, add 5 mL of 10 wt% sodium acetate, then dilute to the scale with water and shake well; in an ultraviolet spectrophotometer, use a 1 cm cuvette, take the iron standard solution as a reference, measure the absorbance value at a wavelength of 510 nm, and find the corresponding iron content on the standard curve;
[0009] S3, calculate the content of iron in lithium iron phosphate:
[0010]
[0011] Wherein, X is the iron content in the sample to be tested, in mg / 100g;
[0012] C is the concentration of iron in the test solution obtained from the standard curve, in ug / mL;
[0013] V1 is the total volume of sample solution for determination, in mL;
[0014] V2 is the total volume of sample dilution, in mL;
[0015] V3 is the volume of the sample solution used for determination, in mL;
[0016] m is the sample mass in g.
[0017] Optionally, in step S1, preparing the test solution specifically includes the steps of: weighing 0.1±0.05 g of the sample to be tested, placing it in a porcelain crucible, carbonizing it on an electric furnace at a first temperature, and then transferring it into a muffle furnace and ashing it at a second temperature until white ash is formed to obtain an intermediate product; adding 5 mL of 1:1 hydrochloric acid solution to the obtained intermediate product, evaporating it to 0.5 mL in a water bath, and then adding 5 mL of water; heating and boiling, transferring it into a 100 mL volumetric flask, diluting it to the scale with water, and shaking it well to obtain the test solution.
[0018] Optionally, the first temperature is 180-200° C., the second temperature is 550-600° C., and the ashing treatment time is 5-10 hours.
[0019] Optionally, the 1:1 hydrochloric acid solution is obtained by mixing concentrated hydrochloric acid with a density of 1.19 g / mL and water in a volume ratio of 1:1.
[0020] Optionally, the method for preparing the standard curve comprises the steps of: measuring 0.0 mL, 1.25 mL, 2.0 mL, 3.0 mL, 4.0 mL, and 5.0 mL of an iron standard solution with a concentration of 100 μg / mL, respectively, and placing them in 50 mL volumetric flasks, adding 5 mL of a 1 mol / L hydrochloric acid solution, 5 mL of a 10 wt % hydroxylamine hydrochloride solution, 5 mL of a 0.12 wt % phenanthroline solution, and 25 mL of a 10 wt % sodium acetate solution, diluting to the scale with water, and shaking well; in an ultraviolet spectrophotometer, using a 1 cm cuvette and a blank solution as a reference, measuring the absorbance value at a wavelength of 510 nm, and drawing a standard curve.
[0021] Optionally, the iron content in the lithium iron phosphate is tested at a temperature of 23±5°C and a humidity of 50±5°C.
[0022] The beneficial effects produced by the present invention include at least:
[0023] The method for testing the iron content in lithium iron phosphate of the present invention comprises the following steps: firstly carbonizing and ashing the sample to volatilize the organic components in the lithium iron phosphate to be tested, thereby improving the purity of the lithium iron phosphate and avoiding interference of other components in the sample to be tested on the subsequent test of the iron content in the lithium iron phosphate; then, hydrochloric acid is added to dissolve the residual metal oxide to further improve the purity of the iron; hydroxylamine hydrochloride is added as a reducing agent and o-phenanthroline is used as a color developer to perform color development, and then an ultraviolet spectrophotometer is used to detect and analyze the iron content in the lithium iron phosphate, and the operation is simple; the dilution multiple of the solution to be tested is small, the fluctuation of the measured value is small, and the stability of the test is improved.
[0024] Hydrochloric acid is added to the intermediate product for dissolution and evaporation in a water bath, thereby ensuring the purity of iron in the lithium iron phosphate to be tested and improving the accuracy of subsequent measurements; when the test method described in the present invention is used to test the iron content in the lithium iron phosphate, the dilution multiple of the solution to be tested is small, the fluctuation of the measured value is small, and the stability of the test is improved; the ultraviolet spectrophotometer is used for testing, the operation method is simple, the requirements on personnel ability are low, the parallelism and stability of the test results are improved, and the test efficiency is improved. DETAILED DESCRIPTION
[0025] For ease of understanding of the present invention, preferred embodiments of the present invention are provided below. However, the present invention can be implemented in many different forms and is not limited to the embodiments described in the present invention. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.
[0026] Unless otherwise defined, all technical and scientific terms used in the present invention have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention.
[0027] It should be noted that the raw materials used in the present invention can be sourced from suppliers known in the art, or prepared by known methods; the iron standard solution described in the present invention is also prepared by known methods.
[0028] The present invention provides a method for testing the iron content in lithium iron phosphate, which comprises the steps of:
[0029] S1, preparing a test solution: carbonizing the test sample at a first temperature, and then ashing the test sample at a second temperature until white ash is formed to obtain an intermediate product; adding a 1:1 hydrochloric acid solution to the intermediate product, and evaporating the solution in a water bath; adding water to the evaporated intermediate product, heating and boiling the intermediate product, transferring the solution to a volumetric flask, and diluting the solution to the scale with water to obtain a test solution;
[0030] S2, determine the iron content in the solution to be tested: measure 5.0 mL of the obtained solution to be tested and place it in a 50 mL volumetric flask, add 1 mL of 1 mol / L hydrochloric acid solution, 1 mL of 10 wt% hydroxylamine hydrochloride, 1 mL of 0.12 wt% o-phenanthroline solution to the volumetric flask, add 5 mL of 10 wt% sodium acetate, then dilute to the scale with water and shake well; in an ultraviolet spectrophotometer, use a 1 cm cuvette, take the iron standard solution as a reference, measure the absorbance value at a wavelength of 510 nm, and find the corresponding iron content on the standard curve;
[0031] S3, calculate the iron content in lithium iron phosphate: the iron content in lithium iron phosphate is calculated according to the following formula:
[0032]
[0033] Wherein, X is the iron content in the sample to be tested, in mg / 100g;
[0034] C is the concentration of iron in the test solution obtained from the standard curve, in ug / mL;
[0035] V1 is the total volume of sample solution for determination, in mL;
[0036] V2 is the total volume of sample dilution, in mL;
[0037] V3 is the volume of the sample solution used for determination, in mL;
[0038] m is the sample mass in g.
[0039] Optionally, in step S1, preparing the test solution specifically includes the steps of: weighing 0.1±0.05 g of the sample to be tested, placing it in a porcelain crucible, carbonizing it on an electric furnace at a first temperature, and then transferring it into a muffle furnace and ashing it at a second temperature until white ash is formed to obtain an intermediate product; adding 5 mL of 1:1 hydrochloric acid solution to the obtained intermediate product, evaporating it to 0.5 mL in a water bath, and then adding 5 mL of water; heating and boiling, transferring it into a 100 mL volumetric flask, diluting it to the scale with water, and shaking it well to obtain the test solution.
[0040] Optionally, the first temperature is 180-200° C., the second temperature is 550-600° C., and the ashing treatment time is 5-10 hours.
[0041] Optionally, the 1:1 hydrochloric acid solution is obtained by mixing concentrated hydrochloric acid with a density of 1.19 g / mL and water in a volume ratio of 1:1.
[0042] Optionally, the method for preparing the standard curve comprises the steps of: measuring 0.0 mL, 1.25 mL, 2.0 mL, 3.0 mL, 4.0 mL, and 5.0 mL of an iron standard solution with a concentration of 100 μg / mL, respectively, and placing them in 50 mL volumetric flasks, adding 5 mL of a 1 mol / L hydrochloric acid solution, 5 mL of a 10 wt% hydroxylamine hydrochloride solution, and 5 mL of a 0.12 wt% phenanthroline solution, and 25 mL of a 10 wt% sodium acetate solution, diluting to the scale with water, and shaking well; in an ultraviolet spectrophotometer, using a 1 cm cuvette and a blank solution as a reference, measuring the absorbance value at a wavelength of 510 nm, and drawing a standard curve.
[0043] Optionally, the iron content in the lithium iron phosphate is tested at a temperature of 23±5° C. and a humidity of 50±5% RH.
[0044] Embodiment 1:
[0045] S1, prepare the solution to be tested: weigh 0.1 g of a uniform lithium iron phosphate sample to be tested, place it in a porcelain crucible, carbonize it on a low fire on an electric furnace at a carbonization temperature of 180°C, transfer it to a muffle furnace and ash it at 550°C for 5 hours until white ash is obtained to obtain an intermediate product; take it out, add 5 mL of a 1:1 hydrochloric acid solution to the intermediate product, evaporate it to dryness in a water bath to 0.5 mL, then add 5 mL of water, heat it to boil, transfer it to a 100 mL volumetric flask, dilute it to the scale with water, shake it well, and obtain the solution to be tested.
[0046] S2, determine the iron content in the test solution:
[0047] 5.0 mL of the obtained solution to be tested was measured and placed in a 50 mL volumetric flask, 1 mL of 1 mol / L hydrochloric acid solution, 1 mL of 10 wt% hydroxylamine hydrochloride, 1 mL of 0.12 wt% o-phenanthroline solution were added to the volumetric flask, 5 mL of 10 wt% sodium acetate was added, and then diluted to the scale with water and shaken well; in an ultraviolet spectrophotometer, a 1 cm colorimetric dish was used, and the iron standard solution was used as a reference, and the absorbance value was measured at a wavelength of 510 nm, and the corresponding iron content was found on the standard curve.
[0048] The method for drawing the standard curve comprises the steps of:
[0049] Accurately measure 0.0mL, 1.25mL, 2.0mL, 3.0mL, 4.0mL and 5.0mL of iron standard solution with a concentration of 100μg / mL and place them in 50mL volumetric flasks respectively, add 5mL of 1mol / L hydrochloric acid solution, 5mL of 10wt% hydroxylamine hydrochloride, 5mL of 0.12wt% o-phenanthroline solution and 25mL of 10wt% sodium acetate to each volumetric flask, then dilute to the scale with water, shake well, and measure the absorbance at a wavelength of 510nm using a 1cm cuvette with a blank reagent in a UV spectrophotometer to draw a standard curve.
[0050] S3, calculate the iron content in lithium iron phosphate: the iron content in lithium iron phosphate is calculated according to the following formula:
[0051]
[0052] Wherein, X is the iron content in the sample to be tested, in mg / 100g;
[0053] C is the concentration of iron in the test solution obtained from the standard curve, in ug / mL;
[0054] V1 is the total volume of sample solution for determination, in mL;
[0055] V2 is the total volume of sample dilution, in mL;
[0056] V3 is the volume of the sample solution used for determination, in mL;
[0057] m is the sample mass in g.
[0058] In this embodiment, the value of V1 is 100 mL, the value of V2 is 50 mL, and the value of V3 is 1 mL. Three portions of lithium iron phosphate to be tested are selected respectively, and the iron in the three portions of lithium iron phosphate to be tested is tested using the above-mentioned test method of the present invention, and each portion of lithium iron phosphate to be tested is tested three times. The test results are shown in the following table.
[0059] Test results table of iron content in the lithium iron phosphate samples to be tested.
[0060]
[0061]
[0062] It can be seen from the above table that the iron content in lithium iron phosphate is tested using the test method described in the present invention. During the test of the iron content in each lithium iron phosphate sample to be tested, the range between the maximum and minimum values is small, with the minimum being 0.04, indicating that the test method described in the present invention has good stability and reliability.
[0063] The technical features of the above embodiments may be combined arbitrarily. To make the description concise, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0064] The above embodiments only express the preferred implementation modes of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for those of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A method for testing the iron content in lithium iron phosphate, characterized in that: Includes steps: S1, preparing a test solution: carbonizing the test sample at a first temperature, and then ashing the test sample at a second temperature until white ash is formed to obtain an intermediate product; adding a 1:1 hydrochloric acid solution to the intermediate product, and evaporating the solution in a water bath; adding water to the evaporated intermediate product, heating and boiling the intermediate product, transferring the solution to a volumetric flask, and diluting the solution to the scale with water to obtain a test solution; S2, determine the iron content in the solution to be tested: measure 5.0mL of the obtained solution to be tested and place it in a 50mL volumetric flask, add 1mL of 1mol / L hydrochloric acid solution, 1mL of 10wt% hydroxylamine hydrochloride, 1mL of 0.12wt% o-phenanthroline solution to the volumetric flask, add 5mL of 10wt% sodium acetate, then dilute to the scale with water, and shake well; in a UV-visible spectrophotometer, use a 1cm colorimetric dish, take the iron standard solution as a reference, measure the absorbance value at a wavelength of 510nm, and find the corresponding iron content on the standard curve; S3, calculate the iron content in lithium iron phosphate: the iron content in lithium iron phosphate is calculated according to the following formula: Wherein, X is the iron content in the sample to be tested, in mg / 100g; C is the concentration of iron in the test solution obtained from the standard curve, in ug / mL; V1 is the total volume of sample solution for determination, in mL; V2 is the total volume of sample dilution, in mL; V3 is the volume of the sample solution used for determination, in mL; m is the sample mass in g.
2. The method for testing the iron content in lithium iron phosphate according to claim 1, characterized in that: In step S1, preparing the test solution specifically includes the steps of: weighing 0.1±0.05g of the sample to be tested, placing it in a porcelain crucible, carbonizing it at a first temperature on an electric furnace, and then transferring it into a muffle furnace and ashing it at a second temperature until white ash is formed to obtain an intermediate product; adding 5mL of a 1:1 hydrochloric acid solution to the obtained intermediate product, evaporating it to 0.5mL in a water bath, and then adding 5mL of water; heating and boiling, transferring it into a 100mL volumetric flask, diluting it to the scale with water, and shaking it well to obtain a test solution.
3. The method for testing the iron content in lithium iron phosphate according to claim 2, characterized in that: The first temperature is 180-200° C., the second temperature is 550-600° C., and the ashing treatment time is 5-10 hours.
4. The method for testing the iron content in lithium iron phosphate according to claim 1, characterized in that: The 1:1 hydrochloric acid solution is obtained by mixing concentrated hydrochloric acid with a density of 1.19 g / mL and water in a volume ratio of 1:
1.
5. The method for testing the iron content in lithium iron phosphate according to claim 1, characterized in that: The preparation method of the standard curve comprises the steps of: measuring 0.0 mL, 1.25 mL, 2.0 mL, 3.0 mL, 4.0 mL and 5.0 mL of an iron standard solution with a concentration of 100 μg / mL respectively and placing them in a 50 mL volumetric flask respectively, adding 5 mL of a hydrochloric acid solution with a concentration of 1 mol / L, 5 mL of hydroxylamine hydrochloride with a concentration of 10 wt % and 5 mL of a 0.12 wt % o-phenanthroline solution, and 25 mL of sodium acetate with a concentration of 10 wt %, diluting with water to the scale, and shaking well; in an ultraviolet-visible spectrophotometer, using a 1 cm colorimetric dish and taking a blank solution as a reference, measuring the absorbance value at a wavelength of 510 nm, and drawing a standard curve.
6. The method for testing the iron content in lithium iron phosphate according to claim 1, characterized in that: The iron content in the lithium iron phosphate is tested at a temperature of 23±5° C. and a humidity of 50±5% RH.
Citation Information
Patent Citations
Method for detecting content of phosphorus and iron in LiFePO4 / C composite material
CN104422665A
Detection method of iron content in lithium iron phosphate
CN105021556A
Method for testing content of iron element in lithium iron phosphate material
CN113533309A